PENGATURAN MENGENAI MAATSCHAP PADA UNDANG-UNDANG JABATAN NOTARIS DAN KITAB UNDANG-UNDANG HUKUM PERDATA TERKAIT TUGAS DAN JABATAN NOTARIS - Bella Patnessia; Gunawan Djajaputra (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2020)
Notary as a general official authorized to create an authentic deed to help create legal certainty. In the law of Notary Number 2 of 2014 on the amendment to Law Number 30 of 2004 on the Department of notary state that notary is allowed to open a notary office in the form of Civil Fellowship. This civil federation will be based on civil fellowship in accordance with the law of the Civil Code. The sense of civil fellowship itself is two or more people wo form an alliance by incorporating something into the compan with the main purpose of seeking profit. So that is the problem appears because on the notary self is not paid but it gets honorarium, beside the problems on independence and also immutability that will be difficult to run when the notary join a civil federation.The research method used is a normative juridicial method of analysis. The techniques of data collection conducted through literature studies and data collection tools are document studies. Data sources of primary data, secondary legal materials, and secondary data are divided into primary legal materials, secondary legal materials, and a tertiary law. The theory used in this research is the theory of legal certainty, and the theory of egal effectiveness.The form of civil partnership that is suitable for public notary is limited to a joint office. So there are no settings and management, there is no need to worry about the conflict and the inequality of the law.